Implications of Online Learning on Students' Cognitive and Emotional Development - Syarifah Aini Kamilah; Cindy Fatikasari Ibrahim; Muhammad Fikri Hasbulloh; Tarsono (al-Afkar, Journal For Islamic Studies, 2025)
Online learning has become a primary choice in the educational process since the COVID-19 pandemic struck. Its impact on students' cognitive and emotional development is the focus of this study. Online learning provides extensive access to digital learning resources, but also poses challenges such as decreased motivation, difficulty understanding material, social isolation, and stress. The transition from face-to-face to online learning brings with it technological adaptation, time management, and student mental health issues. Social support from parents, teachers, and peers is key in helping students overcome emotional challenges. The purpose of this study is to analyze the complex impacts of online learning and emphasize the importance of developing effective learning strategies, psychological support, social interaction, digital skills, and cross-sector collaboration to support students' holistic development. The research method used is a qualitative approach with library research. The results of this study indicate that online learning provides access to various digital learning resources, encourages independent learning, and improves digital skills. However, on the other hand, online learning can lead to decreased learning motivation, difficulty understanding material, social isolation, and stress.